2021
DOI: 10.1021/acs.jcim.0c01054
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Data on Parent Compounds and Their Metabolites from Texts of Scientific Abstracts

Abstract: The growing amount of experimental data on chemical objects includes properties of small molecules, results of studies of their interaction with human and animal proteins, and methods of synthesis of organic compounds (OCs). The data obtained can be used to identify the names of OCs automatically, including all possible synonyms and relevant data on the molecular properties and biological activity. Utilization of different synonymic names of chemical compounds allows researchers to increase the completeness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(35 reference statements)
0
6
0
1
Order By: Relevance
“…It was shown that the half-maximal inhibitory concentration of SARS-CoV-2 Mpro by dihydromyricetin reached 1.76 µM. Additionally, the authors [ 42 ] confirmed the activity of dihydromyricetin on the proteins included in the TGF-β 1/Smad pathway, which are responsible for the development of pulmonary fibrosis.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It was shown that the half-maximal inhibitory concentration of SARS-CoV-2 Mpro by dihydromyricetin reached 1.76 µM. Additionally, the authors [ 42 ] confirmed the activity of dihydromyricetin on the proteins included in the TGF-β 1/Smad pathway, which are responsible for the development of pulmonary fibrosis.…”
Section: Resultsmentioning
confidence: 98%
“…Many various artificial intelligence (AI) approaches aimed at chemical and biological named entity recognition have been developed [ 15 , 18 , 21 ]. Most approaches that have been under recent development for several years are based on the usage of neural networks with different variants of long-short term memory (LSTM) architecture or conditional random fields (CRF) [ 16 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the set of pattern phrases [ 19 ], we obtained a set of interaction maps between human and viral genes and (or) proteins. An example of such an interaction map is provided in Figure 1 for the set of human proteins that can bind or modulate HIV proteins and which most commonly appear in scientific publications.…”
Section: Resultsmentioning
confidence: 99%
“…To identify interactions between pairs of proteins, genes, and protein–gene interactions, we used the rule-based approach described in the study by O. Tarasova et al [ 19 ]. Initially, a set of pattern phrases that indicate association (e.g., “is up-regulated by”) were identified by manual analysis of the text.…”
Section: Methodsmentioning
confidence: 99%